O atrofii kultury literackiej. Uwagi na przykładzie semiotycznych i rzeczowych funkcji książek w filmie Sara - Kaźmierczak, Marek (Przestrzenie Teorii, 2019)
Kaźmierczak Marek, O atrofii kultury literackiej. Uwagi na przykładzie semiotycznych i rzeczowych funkcji książek w filmie Sara [Atrophy of Literature. Remarks about the Semiotic Functions of Books in the Film Sara]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 383–400. ISSN 1644-6763. DOI 10.14746/pt.2019.32.21. The article concerns the relations between the main character of the film Sara (directed by M. Ślesicki in 1997) and books (especially Dostoyevsky’s Crime and Punishment) in the context of social and political changes in Poland in the 1990s. The presence of books in popular Polish films from that period is not described in research, hence this article provides a short introduction to this subject. The main hypothesis of the paper is that the presence of books on the margins of narration in popular films reflects social changes in thinking about literature.